Brand Appeal and Marketing Performance of Instant Noodles Products in Osun State, Nigeria (Journal of Management and Social Sciences, 2025)
The modern consumer goods market has grown to be highly competitive; brand appeal plays a pivotal role in shaping consumer choice and driving product success. This study investigates the influence of brand appeal on the marketing performance of instant noodles products in Osun State, Nigeria. Using a survey design, data were collected from 418 consumers across the state. The study examined three key brand elements: brand name, brand packaging, and brand association. Findings indicate that all three variables are statistically significant and positively affect customer patronage. The model’s R² value of 0.598 suggests that approximately 60% of the variation in customer patronage can be explained by these brand elements combined, reflecting a high explanatory power. Additionally, the F-statistic of 24.380 confirms the overall model’s statistical significance. The study underscores that while all elements are influential, packaging design and quality should be prioritized, followed by consistent advertising and brand image management. Based on the findings, it is recommended that manufacturers enhance their branding strategies by investing in distinctive brand names and engaging packaging that clearly communicates product value. Strengthening brand associations can further boost consumer loyalty and sustain market competitiveness.KeywordsBrand appeal, marketing performance, Instant Noodles, brand packaging, brand association